Turkey's Relations with the Middle East Political Encounters after the Arab Spring (Springer International Publishing, 2018)
This volume examines contemporary political relations between Turkey and the Middle East. In the light of the Arab Uprisings of 2011, the Syria Crisis, the escalation of regional terrorism and the military coup attempt in Turkey, it illustrates the dramatic fluctuations in Turkish foreign policy towards key Middle Eastern countries, such as Iran, Saudi Arabia, Egypt, Syria and Iraq. The contributors analyze Turkey's deepening involvement in Middle Eastern regional affairs, also addressing issues such as terrorism, social and political movements and minority rights struggles. While these problems have traditionally been regarded as domestic matters, this book highlights their increasingly regional dimension and the implications for the foreign affairs of Turkey and countries in the Middle East.